Antioxidant and Anti-inflammatory Properties of Resveratrol in Diabetic Nephropathy: A Systematic Review and Meta-analysis of Animal Studies - Hu, Heng-Chang; Lei, Yuan-Hong; Zhang, Wei-Hua; Luo, Xiao-Qiong (Frontiers in Pharmacology, 2022)
Background: Accumulated experimental evidence suggests that resveratrol may have an effect on diabetic nephropathy by inhibiting inflammation and decreasing oxidative stress. However, the credibility of the evidence for this practice is unclear. Thus, we aimed to perform a systematic review and meta-analysis of animal studies to evaluate the antioxidant and anti-inflammatory properties of resveratrol when used in the treatment of diabetic nephropathy. Methods: Electronic bibliographic databases including PubMed, EMBASE, and Web of Science were searched for relevant studies. The methodological quality of animal studies was assessed based on the SYstematic Review Center for Laboratory animal Experimentation Risk of Bias (SYRCLE’s RoB) tool. A meta-analysis was performed based on the Cochrane Handbook for Systematic Reviews of Interventions by using RevMan 5.4 software. This study was registered within International Prospective Register of Systematic Reviews (PROSPERO) as number CRD42021293784. Results: Thirty-six qualified studies involving 726 animals were included. There was a significant association of resveratrol with the levels of blood glucose (BG), serum creatinine (Scr), blood urea nitrogen (BUN), catalase (CAT), superoxide dismutase (SOD), malondialdehyde (MDA), glutathione (GSH), glutathione peroxidase (GPx), and interleukin-1β (IL-1β). Nevertheless, resveratrol treatment did not effectively decrease the levels of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6). In addition, more remarkable antioxidant and hypoglycemic effects were observed in type 2 diabetic nephropathy rather than in type 1 diabetic nephropathy based on subgroup analysis. Conclusions: In this meta-analysis, resveratrol can exert its antioxidant activities by reducing the levels of MDA and recovering the activities of SOD, CAT, GSH, and GPx. With regard to pro-inflammatory cytokines, resveratrol had a positive effect on the reduction of IL-1β. However, the analysis indicated that resveratrol had no effect on IL-6 and TNF-α levels, probably because of the methodological quality of the studies and their heterogeneity. Current evidence supports the antioxidant and anti-inflammatory properties of resveratrol, but its relationship with the levels of some inflammatory cytokines such as IL-6 and TNF-α in animals with diabetic nephropathy needs further elucidation.